The Correlation Between Uncorrected Myopic Refractive Errors and Patterns of Sports Participation Among Students at Senior High School 15 of West Seram Regency - Dodikrisno E Manery; Ian R Tofure; Ferros Rozik Wakano; Arief Rahman S Kaliky; Yushar A Embisa; Taufik Zuneldi; Abdur Rahman Assagaf; Alfaro Muhammad (PT Pubsains Nur Cendekia, 2026)
Background: Good visual acuity is important for school-aged children; uncorrected myopia can hinder participation in sports, highlighting the need for vision screening and intervention planning in schools. Aim: To examine the association between uncorrected myopic refractive errors and patterns of sports participation among students at SMA 15 West Seram Regency. Methods: This study employed a quantitative cross-sectional study design. A total of 76 students with myopic refractive errors were included as respondents. Data were collected directly using a structured questionnaire that assessed the degree of myopia, type of sports activities, and duration of physical activity. Data analysis was performed using the chi-square test with SPSS to determine the association between the degree of uncorrected myopia and sports activity variables. Results: The findings showed no statistically significant association between the degree of uncorrected myopic refractive error and the type of sports activities performed (p > 0.05), nor with the duration of sports activities (p > 0.05). Although students with mild myopia tended to prefer volleyball and engaged in sports activities for approximately two hours, these tendencies did not demonstrate significant statistical relationships. Conclusion: Uncorrected myopia was not significantly linked to sports type or duration among students, suggesting non-visual factors play a stronger role in adolescents’ participation in school sports activities overall in context.